THE USE OF SECONDARY ALUMINIUM ALLOYS IN TRANSPORTATION ENGINEERING - Volchok, I. P.; Liutova, O. V. (Science and Transport Progress, 2007)
Aluminium alloys are widely used in transport machinery, building and electrical industry. Owing to this reason, considerable volumes of aluminium waste and sсrap are produced. The technology of increasing the density, mechanical and service properties of reusable aluminium alloys is considered in the paper.